Investigation of ADAMTS-13 levels in patients with COVID-19 infection - Hüseyin H Kutlu; Arzu Sahin; Soycan Mizrak; Abdurrahman Yilmaz; Songul Doganay; Serdar Gungor; Sema Yilmaz (Journal of Infection in Developing Countries)
Introduction: Coronavirus disease 2019 (COVID-19) patients are predisposed to thrombotic events. COVID-19 coagulopathy can be associated with ADAMTS-13 (a disintegrin-like and metalloprotease with thrombospondin type I repeats 13) levels. ADAMTS-13, the cleaving protease of highly thrombogenic ultra-large von Willebrand Factor (vWF) multimers, was rarely investigated in COVID-19 patients and inconsistent results were obtained. We measured ADAMTS-13 levels of patients admitted to emergency department.